Educational reforms and marketization in Norway – A challenge to the tradition of the social democratic, inclusive school?. (March 2016) - Helgøy, Ingrid; Homme, Anne
A social democratic, egalitarian public sector and a corporatist political economy have been strong, distinctive and enduring characteristics of Norwegian education. However, this article demonstrates that the education sector has experienced a period of rapid and extensive implementation of New Public Management (NPM) reforms and post-NPM reforms the past 15 years. In contrast to other scholars, who claim that NPM is not contested but rather consistently promoted and maintained by centre-left governments, we argue that from 2005 such governments have added new ideas of government and implemented new methods of steering education in line with post-NPM reforms. To regain central capacity and control and to compensate for the negative effects of NPM on social inclusion and equality, new measures for input control were adopted, and the negative effects of marketization were to some degree moderated by later educational reforms.